Case Report: Ochronotic Arthropathy - Ülkü Dönmez; Ece Cinar; Cihat Ozturk; Simin Hepgüler (Forbes Tıp Dergisi, 2021)
Ochronosis is a rare metabolic disease caused by the deficiency of the homogentisic acid oxidase enzyme. It gives clinical findings related to the accumulation of homogentisic acid in soft tissues and excretion in urine. Patients with chronic arthropathy usually have some joint pain and inflammatory back pain. Although axial involvement radiologically resembles ankylosing spondylitis (AS), it is differentiated by the absence of typical syndesmophytes, facet involvement, sacroiliac erosion and fusion.Although there is no effective treatment for ochronosis disease; our patient was given a protein-poor diet, vitamin C supplementation (100 mg/kg/day) and analgesic treatment for symptoms recommended in the literature; and a reduction in joint complaints was observed. In this case, the aim is to diagnose the rare ochronotic arthropathy followed with the diagnosis of AS and to show that both axial and peripheral joint involvement can be together in this disease.